A clinical evaluation of ceramic inlays bonded with different luting agents - (:unkn) unknown (My University, 2001)
PURPOSE: The purpose of this study was to evaluate the clinical performance of a fired ceramic inlay system bonded with three different luting agents. MATERIALS AND METHODS: A total of 45 Ducera LFC ceramic inlays (12 in premolars, 33 in molars) were placed in 26 patients. Fifteen of the inlays were inserted with one of three different luting agents: (1) Variolink High Viscosity, (2) Enforce, and (3) Geristore. The restorations were evaluated for a period of 3 to 46 months, with a mean of 26.3 months after insertion using modified USPHS criteria. The evaluation period ended when the restoration had to be replaced due to fracture or secondary caries. Postoperative sensitivity was determined by direct questioning. Kaplan-Meier statistical analysis was used to calculate the survival rate of the inlays. Selected restorations were further evaluated indirectly with SEM. RESULTS: The fracture rates observed for Variolink, Enforce, and Geristore were 13%, 13%, and 33%, respectively. There was a high rate of early bulk fracture, seen mainly within 12 months, for inlays luted with Geristore. For all groups, secondary caries was found to be relatively low. The inlays in all luting agent groups showed acceptable color match and surface roughness scores during the whole evaluation period. SEM observation revealed that the deterioration of marginal adaptation was found to be more severe for inlays luted with Geristore, and that the rate of submargination was also higher for Geristore-luted inlays in comparison to those luted with Variolink and Enforce. CONCLUSION: The use of a polyacrylic acid modified glass ionomer, Geristore, resulted in a higher fracture rate and loss of marginal adaptation in fired ceramic inlays. The marginal adaptation of the luting agent was more durable at the enamel interface than that at ceramic interface.
Keywords: Adult; Female; Humans; Male; Survival Analysis; Dental Porcelain; Dental Cements; Statistics, Nonparametric; Dental Bonding; Glass Ionomer Cements; Resin Cements; Dental Marginal Adaptation; Inlays; Resins, Synthetic; Dental Restoration Failure; Cementation